HP55-coated capsule containing PLGA/RS nanoparticles for oral delivery of insulin - Wu, Zhi Min (2013)
In this work, we designed and developed a two-stage delivery system composed of enteric capsule and cationic nanoparticles for oral delivery of insulin. The enteric capsule was coated with pH-sensitive hydroxypropyl methylcellulose phthalate (HP55), which could selectively release insulin from nanoparticles in the intestinal tract, instead of stomach. The biodegradable poly(lactic-co-glycolic acid) (PLGA) was selected as the matrix for loading insulin. Eurdragit® RS (RS) was also introduced to the nanoparticles for enhancing the penetration of insulin across the mucosal surface in the intestine. The nanoparticles were prepared with the multiple emulsions solvent evaporation method via ultrasonic emulsification. The optimized nanoparticles have a mean size of 285 nm, a positive zeta potential of 42 mV. The encapsulation efficiency was up to 73.9%. In vitro results revealed that the initial burst release of insulin from nanoparticles was markedly reduced at pH 1.2, which mimics the stomach environment. In vivo effects of the capsule containing insulin PLGA/RS nanoparticles were also investigated in diabetic rat models. The oral delivered capsules induced a prolonged reduction in blood glucose levels. The pharmacological availability was found to be approximately 9.2%. All the results indicated that the integration of HP55-coated capsule with cationic nanoparticles may be a promising platform for oral delivery of insulin with high bioavailability.